Jedność nauki versus wielość nauk - Menkes, Jerzy (Przegląd Strategiczny, 2012)
Since Middle Ages, a precondition to set apart any discipline and its transformation from real knowledge-science, i.e. theology to current state of the art, has been fighting the conviction of the science unity particular value, shared by all opponents of isolating new disciplines, who derived their approach from Manichean structure of reality-science. Verifying this approach I evoke various, still parallel experience of unsuccessful defence of the international law unity from the fragmentation of law, and subsequently results of partition of law and international law and its impact on the law coherence (including international law) and the coherence of international turnover legal regulation – the long road from law to domestic and international law, from international law to both European and international law, and at present, to (single) law of the European Area.